ANALISIS FAKTOR YANG MEMPENGARUHI PROFITABILITAS PERUSAHAAN ENERGI DI BEI PERIODE 2021-2023 - Moh.Solikul Amin; Siti Alliyah (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to analyze the impact of three main factors – company scale, capital structure and sales growth – on the profitability of companies in the energy sector listed on the Indonesia Stock Exchange from 2021 to 2023. Secondary data, sourced from annual financial reports, is used as the basis for the analysis. The sample consists of 45 companies selected using a purposive sampling method. Data analysis was conducted using a multiple linear regression model after ensuring that the classical assumptions are met. The main results of this study are: company scale is not proven to have a significant relationship with profitability; capital structure has a significant negative effect; sales growth is proven to significantly increase profitability. These findings indicate that efficient capital structure management and sustainable sales growth are important factors in improving the profitability performance of energy sector companies in Indonesia.